2016
DOI: 10.1128/jvi.00190-16
|View full text |Cite
|
Sign up to set email alerts
|

P3N-PIPO, a Frameshift Product from the P3 Gene, Pleiotropically Determines the Virulence of Clover Yellow Vein Virus in both Resistant and Susceptible Peas

Abstract: IMPORTANCEControl of plant viral disease has relied on the use of resistant cultivars; however, emerging mutant viruses have broken many types of resistance. Recently, we revealed that Cl-90-1 Br2 breaks the recessive resistance conferred by cyv1, mainly by accumulating a higher level of P3N-PIPO than that of the nonbreaking isolate Cl-No.30. Here we show that a susceptible pea line recognized the increased amount of P3N-PIPO produced by Cl-90-1 Br2 and activated the salicylic acid-mediated defense pathway, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…Owing to their large population size and short generation time, viruses have a great potential to quickly evolve and adapt under selection pressures [ 102 ]. Host factors (including genetic background), in combination with environmental factors, likely affect virus evolution and adaptation, helping viruses to invade new hosts and potentially form more virulent strains [ 50 , 103 , 104 ]. The durability of deployed resistance genes ultimately depends on the overall evolutionary potential of viruses (which is determined by the genetic structure of viral populations), on the functional flexibility of the pathogen avirulence factors targeted by the resistance gene(s), and on ecological effects which may increase or slow down the emergence of resistance-breaking isolates [ 103 ].…”
Section: The Genetic Background Drives the Evolution Of Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Owing to their large population size and short generation time, viruses have a great potential to quickly evolve and adapt under selection pressures [ 102 ]. Host factors (including genetic background), in combination with environmental factors, likely affect virus evolution and adaptation, helping viruses to invade new hosts and potentially form more virulent strains [ 50 , 103 , 104 ]. The durability of deployed resistance genes ultimately depends on the overall evolutionary potential of viruses (which is determined by the genetic structure of viral populations), on the functional flexibility of the pathogen avirulence factors targeted by the resistance gene(s), and on ecological effects which may increase or slow down the emergence of resistance-breaking isolates [ 103 ].…”
Section: The Genetic Background Drives the Evolution Of Resistancementioning
confidence: 99%
“…Evolutionary constraints upon viral resistance-breaking determinant can be imposed by a trade-off between the breakdown of a recessive resistance gene and host viability regulated by a dominant resistance gene [ 50 , 104 ]. In the pea/ Clover yellow vein virus (ClYVV) pathosystem, Atsumi et al [ 104 ] showed that the recessive gene cyv1 confers resistance to ClYVV and the major viral resistance-breaking determinant is the P3N-PIPO protein. After overcoming the cyv1 resistance, the RB variants accumulate efficiently and produce a more abundant P3N-PIPO that is also a viral effector recognized by the dominant gene Cyn1 , which induces systemic cell-death and the loss of host viability that is unfavorable for the virus.…”
Section: The Genetic Background Drives the Evolution Of Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The leaf tissues of N. benthamiana were homogenized in liquid nitrogen. The total RNA was isolated using the acid guanidinium thiocyanate-phenol-chloroform (AGPC) extraction method [44], then purified on a FARB minicolumn (Favorgen Biotech Corp., Ping-Tung, Taiwan) [45]. Total RNA was digested with Turbo DNase (Thermo Fisher Scientific, Waltham, MA, USA) and reverse transcribed using random hexamer by PrimeScript II reverse transcriptase (TaKaRa Bio), according to the manufacturer's instructions.…”
Section: Bisulfite Sequencingmentioning
confidence: 99%
“…Potyvirus genomes encode an ORF which is translated to a 340–370 kDa polyprotein, which is then co- and/or post-translationally processed by three forms of internally encoded protease into cleavage intermediates or mature protein products ( Figure 1 ). A fusion protein, P3N-PIPO, is read off an alternative open reading frame as a result of a frameshift caused by RNA polymerase slippage on the first ORF [ 133 , 134 ].…”
Section: Potyvirusesmentioning
confidence: 99%